Noninvasive Ventilation with Heliox for Respiratory Distress Syndrome in Preterm Infant: A Systematic Review and Meta-Analysis - Chen Long; Wang Li; Li Wanwei; Li Jie; Shi Yuan (Canadian Respiratory Journal)
Objectives. To assess whether noninvasive ventilation with Heliox reduces the need for endotracheal ventilation and subsequent complications in preterm infants with respiratory distress syndrome (RDS). Methods. A search of major electronic databases, including MEDLINE and the Cochrane Central Register of Controlled Trials, for randomized or quasi-randomized controlled trials that compared noninvasive ventilation with Heliox versus noninvasive ventilation with standard gas for preterm infants with RDS was performed. The primary outcome was the incidence of intubation. The secondary outcomes were the level of PaCO2, the use of surfactant, and other complications. Results. Two randomized and one quasi-randomized controlled trials including 123 preterm infants were assessed. Heliox was found to significantly decrease the incidence of intubation (RR: 0.42; 95% CI: 0.23 to 0.78), the level of PaCO2 (MD: −9.61; 95% CI: −15.76 to −03.45), and the use of surfactant (RR: 0.25; 95% CI: 0.10 to 0.61) as compared with standard gas. No significant differences were found in other secondary outcomes. Conclusions. Noninvasive ventilation with Heliox decreases the incidence of intubation in preterm infants suffering from RDS. However, data on clinical outcomes are limited. Larger trials are needed to verify the beneficial effects.